Antimalarial Activity of Brown Alga Extract Sargassum sp on Liver Cell of Mouse (Mus musculus) Infected with Plasmodium berghei - Ukratalo, Abdul M; Syuaib, Achmad; Pangemanan, Victory O; Embisa, Yushar A; Kaliky, Arief Rahman S; Loilatu, Muhammad Fitrah (PT. Riset Press International, 2025)
Sargassum sp is rich in steroid, alkaloid, phenol, flavonoid, saponin, and tannin components, which have anti-malarial and immunomodulatory properties. This study aimed to assess the anti-malarial effects of an extract from brown algae Sargassum sp on liver cells in Plasmodium berghei-infected house mouse (Mus musculus). Twenty to thirty-gramme house mice were infected with Plasmodium berghei at a dosage of 0.1 ml per tail and monitored until the parasitemia level reached 1-5%. Subsequently, house mice (Mus musculus) were administered methanol extract of brown algae Sargassum sp at 10, 100, and 200 mg/g BW doses for four consecutive days, from day 0 to day 6. On day 6, surgery was performed to extract the liver organ and prepare histological preparations. The findings demonstrated that applying Sargassum sp extract effectively improved the restoration of liver damage in house mice infected with Plasmodium berghei.